2020
DOI: 10.21203/rs.3.rs-19919/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diet-induced Changes in Bacterial Communities in the Jejunum and Their Associations with Bile Acids in Angus Beef Cattle

Abstract: Background: The small intestine, while serving as the main absorption organ, also possesses a unique bacterial environment and holds the critical function of conversion of primary bile acids. Bile acids are, in turn, able to regulate bacterial composition and promote the growth of bacteria that convert primary bile acids to secondary bile acids. However, in beef cattle, few studies have explored the influence of diets on jejunal bacterial communities and examined its relationships with bile acids. Here, we exa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Interestingly, significant differences in the two primary bile acids (cholic acid and taurochenodeoxycholic acid) were observed in ileal mucosa between the HG and HP groups in the present study. A previous study demonstrated that HG diets altered the bacterial communities in the jejunum and significantly decreased the content of cholic acid in bile from cattle ( Liu et al, 2020 ). Another study revealed that high rumen-degradable starch diets significantly increased the hepatic concentration of taurochenodeoxycholic acid in the liver compared with the control group ( Shen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, significant differences in the two primary bile acids (cholic acid and taurochenodeoxycholic acid) were observed in ileal mucosa between the HG and HP groups in the present study. A previous study demonstrated that HG diets altered the bacterial communities in the jejunum and significantly decreased the content of cholic acid in bile from cattle ( Liu et al, 2020 ). Another study revealed that high rumen-degradable starch diets significantly increased the hepatic concentration of taurochenodeoxycholic acid in the liver compared with the control group ( Shen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%